Field notes contributed by Beth and Mark Proescholdt, Liscomb, Iowa, fall 1984 - Proescholdt, Bethet al; Proescholdt, Market al (1984)
Separate field reports contributed by both Beth and Mark Proescholdt, Liscomb, Iowa, fall 1984.These items were used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of fall 1984. Epson - sheet feed